Ore deposit geology - Ridley, John, 1957- (Cambridge University Press, 2013)
"Mapping closely to how ore deposit geology is now taught, this textbook systematically describes and illustrates the major ore deposit types, linking this to their settings in the crust and the geological factors behind their formation. Written for advanced undergraduate and graduate students with a basic background in the geosciences, it provides a balance of practical information and coverage of the relevant geological sciences, including petrological, geochemical, hydrological and tectonic processes. Important theory is summarized without unnecessary detail and integrated with students' learning in other topics, including magmatic processes and sedimentary geology, enabling students to make links across the geosciences. Students are supported by further reading, a comprehensive glossary, and problems and review questions that test the application of theoretical approaches and encourage students to use what they have learnt. A website includes visual resources and combines with the book to provide students and instructors with a complete learning package"--